Competências necessárias para o contador forense no Brasil: percepção de especialistas em fraudes - Caio Lucas Nadone (2017)
The present study had as general objective to find evidences that allow to identify which are the necessary competences for the performance of the forensic accountant in Brazil in the perception of specialists in frauds. To do so, the studies of Digabriele (2008) were examined; Davis, Farrell and Ogilby (2010); Okoye and Jugu (2010); Astutie and Utami (2013) and Bhasin (2013), in order to identify the skills for the forensic accountant. The term competence was defined as the set of knowledge, skills, abilities and other characteristics. This definition was based on the Green model (1999) KSAO - Knowledge, Skill, Ability, Other. The research methodology was predominantly quantitative and as strategy the Delphi technique was used, which consists of a questionnaire that circulates several times in a group of experts in order to obtain a consensus on a certain subject. By means of the literature review, 23 competences required for the performance of the forensic accountant were collected and later submitted to the Delphi group of specialists. The built-in questionnaire was based on these competencies and was applied to 20 fraud specialists. In the first stage of the process, the committee of experts agreed with all the competencies evidenced in the literature and also suggested 14 new competences, through their knowledge and experiences, which were included in the next step. In the second round, first, the results of the previous round were presented. Next, the experts were asked to evaluate the competences in grade of importance assigning grades from 0 to 10. In the third and last round, again, feedback was sent to the participants, presenting the results of the second round synthesized by means of descriptive statistics . Subsequently, the respondents were asked if they would like to re-evaluate their scores using the evidence. At the end of the application of the Delphi technique, it was possible to elaborate a classification for the competences investigated. As main results, it was verified that all competencies raised in the literature are necessary for the forensic accountant's performance. In addition, Delphi specialists have proposed 14 new skills for the forensic accounting professional. In this context, the five competencies with the best classification are those that have obtained more than 95% of the score, being: impartiality, understanding of the objectives of a case, investigative flexibility, critical thinking and unstructured problem solving. On the other hand, the knowledge competence in psychology obtained a score of 69%, being the lowest by the expert committee. It should be noted that the results of the research can assist in the training of forensic accountants, providing bases for the creation of curricular degrees for undergraduate or graduate courses in universities, as well as training and professional courses in Forensic Accounting.